Observation of a Class of Disturbance in Time Series Expansion for Fractional Order Systems. (17th March 2014) - Wei, Yiheng; Karimi, Hamid Reza; Pan, Jinwen; Gao, Qing; Wang, Yong
Abstract : This paper is concerned with the problem of designing disturbance observer for fractional order systems, of which the disturbance is in time series expansion. The stability of a special observer with the selected nonlinear weighted function and transient dynamics function is rigorously analyzed for slowly varying disturbance. In addition, the result is also extended to estimate slope forms disturbance and higher order disturbance of fractional order systems. The efficacy of the proposed method is validated through numerical examples.